OP0156 Epigenetic Silencing of Endogenous WNT Inhibitors Contributes to the Aberrant Activation of Canonical WNT Signaling in Systemic Sclerosis. (23rd January 2014) - Dees, C.; Schlottmann, I.; Funke, R.; Distler, A.; Palumbo-Zerr, K.; Zerr, P.; Lin, N.-Y.; Beyer, C.; Distler, O.; Schett, G.; Distler, J.
Abstract : Background: Aberrant activation of the Wnt pathway with decreased expression of endogenous antagonists has recently been characterized as central pathomechanism in systemic sclerosis (SSc). Epigenetic alterations have been shown to contribute to the persistent activation of SSc fibroblasts. However, a functional relationship between Wnt signaling and epigenetics in SSc have not been established. Objectives: The molecular mechanisms leading to the decreased expression of endogenous Wnt antagonists is incompletely understood. This study aimed to investigate whether increased Wnt signaling and epigenetic changes in SSc are causally linked via promoter hypermethylation induced silencing of Wnt antagonists. Methods: Activation of Wnt signaling was assessed by analyzing Axin2 mRNA levels and by staining for β-catenin. The methylation status of endogenous Wnt antagonists in fibroblasts was evaluated by methylation-specific PCR and the expression was assessed by real-time PCR, immunohistochemistry and Western Blot. 5-aza-2-deoxycytidine (5-aza) was used to inhibit DNA methyltransferases (Dnmts) in cultured fibroblasts and in the mouse model of bleomycin-induced skin fibrosis. Results: Significant hypermethylation of the promoters of DKK1 and SFRP1 was found in cultured fibroblasts from SSc patients resulting in decreased gene transcription by 66 % for DKK1 and by 72 % for SFRP1 compared to fibroblasts from healthy individuals (p < 0.05 for both). Consistently the protein levels of both proteins were strongly decreased in skin of SSc patients. Treatment of fibroblasts with 5-aza re-activated the transcription of DKK1 and SFRP1 in SSc fibroblasts and increased the expression of DKK1 and SFRP1 to the levels of control fibroblasts (p < 0.05 each). Similar results were observed in murine models of fibrosis. In the model of bleomycin-induced dermal fibrosis, the mRNA levels of DKK1 decreased by 73 % (p = 0.036) upon bleomycin challenge and those of SFRP1 by 35 % (p = 0.004). Both genes were re-activated by treatment of bleomycin-challenged mice with 5-aza. These results were confirmed on the protein level. Consistent with re-activated expression of DKK1 and SFRP1, treatment with 5-aza efficiently reduced nuclear accumulation of β-catenin and decreased the expression of the Wnt target gene Axin2, both in vitro and in vivo. Finally, application of 5-aza prevented bleomycin-induced dermal fibrosis with decreased dermal thickening by 84 % (p = 0.0002) and efficient reductions in myofibroblast counts and hydroxyproline content by 61 % and 75 % (p = 0.0002 and p = 0.004). Conclusions: We demonstrate that promoter hypermethylation of DKK1 and SFRP1 contributes to aberrant Wnt signaling in SSc. These data provide a novel link between epigenetic alterations and increased Wnt signaling in SSc and might have translational implications, because inhibitors of DNA methyltransferases are already approved for clinical use and are therefore available for clinical trials in SSc patients. Disclosure of Interest: None Declared